1995
DOI: 10.1128/jvi.69.12.7759-7767.1995
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the 72-kilodalton human cytomegalovirus IE1 gene product with E2F1 coincides with E2F-dependent activation of dihydrofolate reductase transcription

Abstract: Three polypeptides are produced from the major immediate-early (IE) region of human cytomegalovirus by alternative splicing. The IE gene products regulate subsequent viral and cellular gene expression. We previously reported that cotransfection of a genomic clone of the major IE region stimulated transient expression of chloramphenicol acetyltransferase driven by the dihydrofolate reductase (DHFR) promoter and that an intact E2F site was required for the trans activation (M. Wade, T. F. Kowalik, M. Mudryj, E.-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 97 publications
(122 reference statements)
2
39
1
Order By: Relevance
“…Our findings are somewhat surprising in that the expression of genes affected by IE1 was expected to be upregulated rather than downregulated, because IE1 has been known to be a transactivator of various cellular and viral promoters (Stenberg and Stinski, 1985;Tevethia et al, 1987;Davis et al, 1987;Cherrington and Mocarski, 1989;Sambucetti et al, 1989;Stenberg et al, 1989;Iwamoto et al, 1990;Hagemeier et al, 1992;Monick et al, 1992;Michelson et al, 1994;Margolis et al, 1995;Yur-ochko et al, 1995;Kim et al, 1999;Murayama et al, 2000). However, most affected genes harbored in the cDNA chip were downregulated by the IE1 protein.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our findings are somewhat surprising in that the expression of genes affected by IE1 was expected to be upregulated rather than downregulated, because IE1 has been known to be a transactivator of various cellular and viral promoters (Stenberg and Stinski, 1985;Tevethia et al, 1987;Davis et al, 1987;Cherrington and Mocarski, 1989;Sambucetti et al, 1989;Stenberg et al, 1989;Iwamoto et al, 1990;Hagemeier et al, 1992;Monick et al, 1992;Michelson et al, 1994;Margolis et al, 1995;Yur-ochko et al, 1995;Kim et al, 1999;Murayama et al, 2000). However, most affected genes harbored in the cDNA chip were downregulated by the IE1 protein.…”
Section: Discussionmentioning
confidence: 69%
“…This 72-kDa phosphoprotein is abundantly expressed immediately after infection (Plachter et al, 1996). In transient transfection assays, IE1 has been shown to be involved in the autoregulation of its own promoter and also in the transactivation of viral and cellular promoters, alone or in concert with other viral or cellular proteins (Stenberg and Stinski, 1985;Davis et al, 1987;Tevethia et al, 1987;Cherrington and Mocarski, 1989;Sambucetti et al, 1989;Stenberg et al, 1989;Iwamoto et al, 1990;Hagemeier et al, 1992;Monick et al, 1992;Michelson et al, 1994;Margolis et al, 1995;Yurochko et al, 1995;Kim et al, 1999;Murayama et al, 2000). It was also reported that the IE1 gene product could cooperate with another IE gene product, IE2, and adenoviral E1A to transform primary baby rat kidney (BRK) cells (Shen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…IEp72 is known to be a DNA-binding protein, with regulatory functions on viral gene expression [Isomura and Stinski, 2003]. Furthermore, it is able to interfere with several cellular processes, including gene regulation, cell cycle progression, signal transduction, apoptosis, interaction with specific nuclear domains, such as promielocytic leukemia (PML) bodies [Margolis et al, 1995;Zhu et al, 1995;Wilkinson et al, 1998;McElroy et al, 2000;Castillo and Kowalik, 2002]. Specifically, IEp72 was previously reported to accumulate in PML bodies and to trigger their disruption about 4 h after infection [Kelly et al, 1995;Ahn and Hayward, 1997;Muller and Dejean, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HCMV is similar to adenovirus (E1A oncoprotein), SV40 (large T antigen), papillomavirus (E7 oncoprotein) and EBV nuclear antigen 3C in targeting this pathway [65][66][67][68]. Furthermore, IE72 directly interacts with E2F1 [69] and its inherent kinase activity is also believed to phosphorylate p107 and p130 (but not pRb) releasing the E2F4 family member, and, through a direct interaction, phosphorylates E2Fs À1, À2 and À3. This leads to stimulation of cellular DHFR expression to maintain abundant resources within the cell for the virus to exploit for high-level viral DNA synthesis [59].…”
Section: The Effects Of the Major Ie Proteinsmentioning
confidence: 99%